Pembuatan Kerajinan Bunga Berbahan Kulit Jagung Ditinjau dari Prinsip-prinsip Seni Rupa dan Kerajinan - Astari Utami; Heri Soeprayogi; Adek Cerah Kurnia Azis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to determine the work of flowers made of corn husk on the work of students of class X MS 1 and X SOS 2 of SMA Negeri 1 Kabanjahe. The limitation of the problem in this study focuses on the work of flowers made of corn leather with the review of the principles of fine arts and  crafts . The population in this study were grade X students of SMA Negeri 1 Kabanajahe, with 352 students divided into 7 classes for X MS and 4 classes for SOS X. In this study the authors took a sample of 1 class for class X MS 1 and X SOS 2 with a total of 32 works using the Clusster Random Sampling technique. The reason is because the number of students is too much so the author limits the sample by comparing the work of students of class X MS 1 with students X SOS 2. In this study the writer will examine the work of flower craft made from corn skin based on the principles of fine arts and crafts. The method used in this research is qualitative descriptive method. Data collection techniques used are the work of students' crafts, documentation and observation. The results showed that the work of corn husk craft in class X SMA N 1 Kabanjahe in terms of the fine arts and craft principles of class X MS 1 students obtained an average number of grades 80.47 categorized well while class X SOS 2 students received an average grade of an average of 78.60 with a good category.